2018
DOI: 10.3892/ol.2018.7893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin glucosides from Allium extracts on HepG2, PC‑3 and HT‑29 cancer cell lines

Abstract: Abstract. The present study investigated the effects of quercetin glucosides, which were isolated from the Chinese onion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Despite the differences in the volatile sulfur composition, many components are highly similar for both species, as expected, since they are genetically closely related [38]. The volatile sulfur compounds identified in current study are known to be responsible for typical flavor and odor of onions [27,39], as well as for their strong biological activity [17,[40][41][42][43][44]. Some of the relevant Allium species with their volatile sulfur compounds are described in the following section (Data S2).…”
Section: Nosupporting
confidence: 61%
See 1 more Smart Citation
“…Despite the differences in the volatile sulfur composition, many components are highly similar for both species, as expected, since they are genetically closely related [38]. The volatile sulfur compounds identified in current study are known to be responsible for typical flavor and odor of onions [27,39], as well as for their strong biological activity [17,[40][41][42][43][44]. Some of the relevant Allium species with their volatile sulfur compounds are described in the following section (Data S2).…”
Section: Nosupporting
confidence: 61%
“…The antiproliferative activity of Allium species seems to be related with the synergistic effect of various phytochemicals present in their bulbs of leaves, especially flavonoids and sulfur compounds. Two most abundant flavanols in onion species, quercetin 3,4 -diglucoside and quercetin 4 -monoglucoside, have shown the ability to suppress cell proliferation in three cancer cell lines, HepG2, PC-3, and HT-29 [42]. Similarly, the combination of quercetin and kaempferol was able to reduce cell proliferation in human gut (HuTu-80 and Caco-2) and breast cancer cells (PMC42), which is the evidence of the synergistic effect of phytochemicals isolated from different vegetables used in the human diet [58].…”
Section: Antiproliferative Activity Of a Cornutum And A Cepa Extractsmentioning
confidence: 99%
“…The antiproliferative effect of onion in breast cancer cells is mediated by inhibiting 25 phosphatase with the help of natural tetra sulfide compounds that consequently block cell cycle (Cheng et al, ; Khan et al, ; Ying et al, ). Results have shown that although onion had no considerable toxic effects on HepG2, HT29, and PC3 cell lines, but its quercetin glucosides especially 4′Qmg exhibited significant anticancer activities on these cell lines (Pan et al, ). Perhaps it could be claimed that quercetin and fisetin have the most important role in controlling cancer by onions (Nijveldt et al, ).…”
Section: A Cepamentioning
confidence: 99%
“…These nutritive greens, especially garlic, are associated with a reduced risk of prostate cancer (Chhabra et al, 2018;Nicastro, Ross, & Milner, 2015). Assessing the in vitro and in vivo anticancer activities of Allium species showed that high-volume intake of Allium genus like garlic has prophylaxis effects, which reduces the risk of breast, colon, stomach, and prostate cancers (Miraghajani, Rafie, Hajianfar, Larijani, & Azadbakht, 2018;Pan, Zheng, & Ho, 2018). A study by Chen et al among Taiwanese patients showed that consumption of garlic and onion at least once a week reduced the chance of esophageal cancer (Chen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This action reflected the antitumor impact of the extract on the solid tumors. An in vitro study of the Allium extracts cytotoxic effect against cancer cells was performed by Pan et al [40]. They attributed this cytotoxic effect to the presence of high phenolic compounds such as quercetin glucosides.…”
Section: Discussionmentioning
confidence: 99%